Kinerja Keuangan Sebelum dan Sesudah Akuisisi PT. Indomobil Sukses Internasional Tbk - Rina Masitoh Haryadi, Achmad Wibowo Santoso, Elfreda Aplonia Lau, (EKONOMIA, 2015)
Globalization and free competition requires every company to constantly develop strategies in order to survive, thrive and competitiveness. One strategy that can be taken by the company is an acquisition. The goal is to obtain synergies to maximize profit and reduce the risk simultaneously. In this research study about the comparison of financial performance before and after the acquisition by using Economic Value Added (EVA). Where the object of the research is PT. Indomobil Sukses Internasional Tbk. which was acquired by Gallant Venture Ltd. at 13 December 2012. The financial performance which became the object of research are the pre-acquisition financial performance in 2012 and financial performance after the acquisition in 2013The results showed that the financial performance of PT. Indomobil Sukses Internasional Tbk. measured by the method of Economic Value Added (EVA) both before and after the acquisition EVA of the company is negative. Net Operating Profit After Tax (NOPAT) obtained by the company decreased and on the other side of Weighted Average Cost of Capital (WACC) and the total assets owned by the company increase. EVA of the company after the acquisition is lower than before the acquisition caused by the Cost of Capital is borne by the company have increased but NOPAT acquired by the company decreased, the culture shock caused by differences in work culture, and the acquirer company who does not have experience in the automotive industry.